2017
DOI: 10.1117/1.jmi.5.1.011015
|View full text |Cite
|
Sign up to set email alerts
|

Combining multiparametric MRI with receptor information to optimize prediction of pathologic response to neoadjuvant therapy in breast cancer: preliminary results

Abstract: Pathologic complete response following neoadjuvant therapy (NAT) is used as a short-term surrogate marker of eventual outcome in patients with breast cancer. Analyzing voxel-level heterogeneity in MRI-derived parametric maps, obtained before and after the first cycle of NAT ([Formula: see text]), in conjunction with receptor status, may improve the predictive accuracy of tumor response to NAT. Toward that end, we incorporated two MRI-derived parameters, the apparent diffusion coefficient and efflux rate consta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…The top 4 texture features were then included as predictors in the final logistic ridge regression models. Because of the number of subjects being fewer (n = 28) than the number of explanatory variables, we used logistic ridge regression models to avoid overfitting ( 10 , 11 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The top 4 texture features were then included as predictors in the final logistic ridge regression models. Because of the number of subjects being fewer (n = 28) than the number of explanatory variables, we used logistic ridge regression models to avoid overfitting ( 10 , 11 ).…”
Section: Methodsmentioning
confidence: 99%
“…In each logistic ridge regression, the tuning parameter was estimated as described in by Cule et al ( 12 ). The performance of the 3 models was compared in terms of overfitting-corrected AUC (area under the receiver operating characteristic [ROC] curve) and Brier scores ( 11 , 13 ).…”
Section: Methodsmentioning
confidence: 99%
“…For this reason, it is not surprising that studies evaluating early response after a single cycle of therapy have found success with multiparametric models combining pharmacokinetic DCE-MRI and diffusion-weighted (DWI) MRI, yielding high areas under the curve (AUCs) of 0.88-0.94. 23,24 A study evaluating changes in DWI at seven timepoints through treatment found that changes in the apparent diffusion coefficient (ADC) between baseline and either timepoints 1 or 2 were FIGURE 3: A 59-year-old woman with invasive ductal carcinoma (triple-negative). (a) Prior to neoadjuvant therapy, early-phase postcontrast T 1 -weighted image demonstrate a 3.0 cm mass in the superior breast (arrow).…”
Section: Enhancement and Pharmacokinetic Assessment Of Treatment Respmentioning
confidence: 99%
“…The MRI approach in question seems to accurately predict a treatment response right after a single cycle of therapy. Moreover, this method may improve the accuracy of evaluating a tumor’s response to NAT, showing a higher predictive power than models based on tumor size changes, and it may be used as a short-term surrogate marker of outcome in breast cancer patients [122].…”
Section: Magnetic Resonance Imaging Sequences In the Translationalmentioning
confidence: 99%